Influence of Interfaith Dialogue on Social Cohesion in Multi-Cultural Societies in India - Reddy, Neha (International Journal of Culture and Religious Studies, 2025)
Purpose: The purpose of this article was to analyze influence of interfaith dialogue on social cohesion in multi-cultural societies in India. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Interfaith dialogue in India enhances social cohesion by promoting mutual understanding and reducing religious tensions. It fosters social trust and community integration, particularly in urban areas with diverse religious groups. While challenges persist in rural regions, interfaith initiatives are crucial for bridging divides and improving inter-group relations. Overall, such dialogue strengthens social cohesion but requires ongoing engagement and inclusive spaces Unique Contribution to Theory, Practice and Policy: Social identity theory, contact theory & theory of social capital may be used to anchor future studies on the influence of interfaith dialogue on social cohesion in multi-cultural societies in India. In practice, fostering interfaith dialogue can take the form of organized events, community service projects, and religious education programs that bring together individuals from different faith backgrounds. At the policy level, governments can play a crucial role in promoting interfaith dialogue through funding and creating supportive frameworks for interfaith initiatives.